Pengaruh Motivasi Kerja Dan Pelatihan Terhadap Kinerja Karyawan Bus Damri Bandara Soekarno Hatia Sebagai Transportasi Antarmoda - Noviyanti, Noviyanti (Sekretariat Badan Penelitian dan Pengembangan Perhubungan, 2010)
Bus Senrice Performance Damri which is a passenger transportation at the airport in terms of several.attributes, not only measured at the time of tire tnp 7ms the bus Danrri only. One factor thnt alsodetermines tire leuel of sen1ice pafor111n11cr is 11ssocintr1I wit/1 co11ifort, sernrity and tinre trmd journettook when the senrice user was at the airport to replna: tire uelzicle or changing nwdes of transportationin order to conh.nue his journei;, nnd the m1ailnbilihJ of transport continued to be used to reachthe final. destinntion or uice versn. Impraued performance of passenger transport services continued/multimoda can be seen from the driver's behnvi.or in senn.ce to passengers, the ease of passengertransport continued to I from the Jwmda Airport Suknmo Hatta and m1ai.lnbility of transportationfacilities to senie demand antamwdn sen1ice /passenger transport continued. Achieving imprmiementof entplotjee sen1ice perfomumce On111ri h11s Suknmo Hnttn ns passenger transport, the fulfillmentsenrice facilities proportionately, the right target and meclmnism antarmoda transportationsenrices and met the standard requirements Antamwdn Transportation senrice facilities in SoekamoHatta Airport is a ven; expected. To detemzine the effect of emplot;rnent and training motivas ki.nejaconducted a sun'elJ of 60 ernplm;ees Damri and annlyzed m; using correlntive annlysis model, theresearch result of a strong and pos1ti11e relations/zip between work motimtion 71nth the efforts ofworkers, there is a strong and positive relationship between enrplot;ee training with Enrplot;ee Performance,and the presence of a strong and positi11e relations/zip between nwtimtion work with Emplot;ee Training jointly unth Emplm;ee Perfommnce.Keywords: Work motimtion and training, Sennce Performance